A SYSTEMATIC AND ACTIVITY-BASED APPROACH IN TEACHING RUSSIAN AT HIGHER EDUCATION INSTITUTIONS - Radjabova Lyubov Usmanovna (International Engineering Journal For Research & Development, 2020)
The article is devoted to questions of realization of the system-operative approach in teaching of Russian language in higher education institutions, productive work of use by students of reference books (dictionaries) on lessons.